Umbilicus and Umbilical Cord - Fahmy, Mohamed (Springer International Publishing, 2018)
This book discusses the importance of umbilical cord and umbilicus as a unique structure, in health and in different diseases. All congenital anomalies of the umbilical cord as well as acquired diseases are explained and discussed with illustrations and animations. Starting from complications during and after birth, the book then covers childhood and adolescent umbilical abnormalities. Conditions such as umbilical stump diseases and anomalies, gastroschisis, omphalocele and urachal anomalies are discussed and explained, highlighting recent advances in their management. Among the contents are also chapters offering a cultural and historical perspective to the topic. Written by a top pediatric surgeon this book brings decades of practical knowledge to readers, highlighting the importance of the umbilicus in development and childhood health.